Phylogenetic signal analysis in the basicranium of Ursidae (Carnivora, Mammalia) - Arnaudo, Maria Eugenia (2019)
Ursidae is a monophyletic group comprised of three subfamilies: Tremarctinae, Ursinae and Ailuropodinae, all of which have a rich geographical distribution. The phylogenetic relationships within the Ursidae group have been underexamined, especially regarding morphological traits such as the basicranium. Importantly, the basicranium is a highly complex region that covers a small portion of the skull, combining both structural and functional aspects that determine its morphology. Phylogenetic hypotheses of the Ursidae (including Tremarctinae) have been made based on morphological characters that considers skull, mandible and teeth features, while specific characters of the auditory region and basicranium have not been taken into account. To do this, we analyse the shape and size macroevolution of the basicranium of Ursidae, testing its morphological disparity in a phylogenetic context, which is quantified by means of the phylogenetic signal. We investigated phylogenetical autocorrelation by shape (depicted by Principal Components Analysis scores from previous published analyses) and basicranium size (depicted by centroid size, CS) using an orthonormal decomposition analysis and Abouheif C mean. The main advantages of these methods are that they rely exclusively on cladogram topology and do not require branch-length estimates. Also, an optimisation of the ancestral nodes was performed using TNT 1.5 software. In relation to the phylogenetic signal, both methods showed similar results: the presence of autocorrelation was detected in PC1 and PC2, while in PC3, PC4 and PC5 and in the size of the basicranium (CS), the absence of autocorrelation occurred. The most significant nodes (where there is autocorrelation) are the basal nodes ´Ursidae´ and ´Ursinae-Tremarctinae´. Within this last group, distinctive basicranium morphology is observed, being more conservative in Tremarctinae than in Ursinae. The differences between these subfamilies could be related to historical events involving varying food and environmental preferences. The high phylogenetic signal in the node Tremarctinae probably indicates that the basicranium configuration of these bears was obtained early in their evolutionary history. Finally, our results of the basicranium and skull length ratios indicate that in Tremarctinae, the basicranium size was not determined by phylogeny but instead by other factors, such as adaptive responses to climatic changes and competition with other carnivores.